Collaborative Video Project in English Online Learning: Challenges and Benefits - Maryani, Maryani; Aguskin, Lewinna C. (Celt: A Journal of Culture, English Language Teaching & Literature, 2023)
Cooperative foreign language learning can be achieved by creating a video in a group. The purpose of this study is to discover university students’ perception of the implementation of creating collaborative video projects in English online learning during the pandemic situation. This study seeks to answer two research problems: first, the challenges that students face in the process of video creation; second, the benefits that they obtain from the video project. The data was contributed by 83 English Department students in a private university in Indonesia. For their final project, the participants were asked to create a group video related to the topics of learning materials. Two types of data collection were used in the study namely the open-ended questionnaire and the videos as the final products. Thematic analysis was used to analyze the qualitative data. The findings show that students have faced several challenges in creating videos, especially technical preparation and time management; however, they have also benefited from the video project as they were immersed in autonomous learning. This study demonstrates that a video project is needed as it helps to foster students’ creativity, teamwork, and English language development.